2010
DOI: 10.3354/dao02185
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Japanese flounder Paralichthys olivaceus from viral hemorrhagic septicemia (VHS) by Poly(I:C) immunization

Abstract: In immunization of fish with polyinosinic-polycytidylic acid (poly[I:C], a synthetic double-stranded RNA), injection of Poly(I:C) followed by challenge with a live virus induces a transient, non-specific antiviral state by interferon activity. When exposed to a virus while in this antiviral state, the fish acquire a specific and protective immunity against the corresponding viral disease and survive. In the present study, the effiacy of Poly(I:C) immunization was investigated in japanese flounder Paralichthys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…The antiviral state inhibits the replication of DNA and RNA viruses [37]. This has been observed in both in vitro and in vivo studies in mammals and fish [18,37,41]. Poly I:C can induce an antiviral state in both fish and fish cell lines.…”
Section: Introductionmentioning
confidence: 89%
“…The antiviral state inhibits the replication of DNA and RNA viruses [37]. This has been observed in both in vitro and in vivo studies in mammals and fish [18,37,41]. Poly I:C can induce an antiviral state in both fish and fish cell lines.…”
Section: Introductionmentioning
confidence: 89%
“…Several studies using ELISA systems for the detection of specific fish antibodies have been reported for aquatic animals (Jorgensen et al 1991;Yoshimizu et al 1992;Dixon et al 1994;Pilström 1994, 1995;LaPatra 1996;Nishida et al 1998;Watanabe et al 1998;Swain and Nayak 2003;Okuda et al 2006;Kim et al 2007Kim et al , 2008Kim et al , 2009Takami et al 2010). However, use of an ELISA for fish antibody detection can be problematic because of difficulties such as low reproducibility, which is partly due to high background optical density (OD) caused by nonspecific reactions between fish antibodies and antigens Pilström 1994, 1995;Knopf et al 2000;Kibenge et al 2002;Guo and Woo 2004).…”
mentioning
confidence: 98%
“…Unfortunately, almost no live virus vaccines for fish have been investigated, except our previous studies [17][18][19][20][21][22][23][24]; one of the reasons could be due to the possibility of viral spread from vaccinated fish into the aquaculture environment. Thus, we investigated the possibility of horizontal infection from fish with the live NNV vaccine to naïve fish by cohabitation.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, surviving fish can mount a protective immune response against NNV [21]. It is conceivable that these live vaccine concepts will eventually be applicable to a wide range of fish species as well as other viruses [22][23][24].…”
Section: Introductionmentioning
confidence: 97%